Changes in Platelet Functions, Coagulation and Fibrinolysis in Uncomplicated Cases of Acute Myocardial Infarction - Bjerre Knudsen, J; Gormsen, J; Skagen, K; Amtorp, O (Thrombosis and Haemostasis, 1979)
Platelet aggregation and serotonin-release in vitro and some coagulation and fibrinolysis parameters were studied closely in 12 patients with non-complicated acute transmural myocardial infarction from the very beginning, for 3 weeks.The aggregability with ADP, epinephrine and collagen and the serotonin-release was significantly reduced the first days. Significantly increased aggregability and serotonin-release developed after a week, with peak activity on days 14–16. Most patients still exhibited increased activity at the discharge on days 21–22.Positive ethanol gelation tests developed after day 1 in most patients with a peak at day 5, contemporary with peak activities of factor VIII and negatively correlated to factor XIII activity, quantitated biologically. These values were normalized on discharge. Antithrombin III (Xa) remained unchanged, normal to slightly elevated.The fibrinolytic activity decreased after day 1 with lowest activity on day 5, contemporary with peak activity of antiplasmin. Around 50% of the patients showed decreased activity on discharge.